Antibacterial and Antifungal Activities of the Leaf Extracts of Mentha piperita L. - Jeffrey Jeffrey; Dewi Lidya Ichwana Nasution; Myrna Nurlatifah Zakaria; Anisa Fitriani; Aurorin Silvia Junir (Faculty of Medicine, Universitas Padjadjaran, 2026)
Herbal medicines are increasingly used due to the presence of bioactive compounds with antibacterial and antifungal properties. This study aimed to evaluate the antibacterial and antifungal effects of Mentha piperita L. extract against Porphyromonas gingivalis and Candida albicans. A laboratory-based experimental study with a post-test only control group design was conducted. The test organisms were exposed to M. piperita L. extract at concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%. The antibacterial and antifungal activities were evaluated using the agar well diffusion method to determine inhibition zones, followed by broth dilution tests to identify the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and Minimum Fungicidal Concentration (MFC). Statistical analysis was performed using one-way ANOVA with a significance level of p<0.05. Results showed that all concentrations inhibited the growth of both microorganisms, with MIC values of 12.5% and 25% for P. gingivalis and C. albicans, respectively. The MBC for P. gingivalis and MFC for C. albicans were both observed at 100%. There were significant differences (p<0.05) in the inhibition zones across the concentrations tested. In conclusion, Mentha piperita L. extract demonstrates significant antibacterial and antifungal activities against Porphyromonas gingivalis and Candida albicans, suggesting its potential as a natural antimicrobial agent for oral infections.